An unusual origin of the celiac trunk and the superior mesenteric artery in the thorax. Issue 8 (20th September 2013) - Matusz, Petru; Iacob, Nicoleta; Miclaus, Gratian D.; Pureca, Ana; Ples, Horia; Loukas, Marios; Tubbs, R. Shane
<x xml:space="preserve">Abstract</x> The authors report a case of a 44‐year‐old male found to have unusual origins of the celiac trunk (CT) and superior mesernteric artrery (SMA) as revealed by routine multidetector computed tomograph (MDCT) angiography. The CT and SMA originate from the thoracic aorta (TA) 21 mm and 9 mm above the aortic hiatus, respectively. The median arcuate ligament (MAL) is located at the level of the L1–L2 intervertebral disc. The course of the CT descends in the thoracic cavity making a 14° acute downward angle in front of the TA; below the level of the MAL, the CT descends, making an angle of 47°. The course of the SMA descends at both the thoracic and abdominal level making an angle of 17°, and having an aortomesenteric distance of 9 mm at the level of the third part of the duodenum. In the present case, the supradiaphragmatic origin of the CT and the SMA was determined by their incomplete caudal descent, associated with a pronounced apparent descent of the diaphragm. A thoracic origin of the CT and SMA and the acute downward aortomesenteric angle (17°) associated with a reduced aortomesenteric distance at the level of the third part of the duodenum (9 mm), although no clinical signs are present, may predispose the patient to develop simultaneously a triple syndrome: the compression of CT by MAL (celiac axis compression syndrome), the compression of SMA by MAL (superior mesenteric artery compression syndrome), and the compression of the duodenum by the SMA (superior mesenteric artery syndrome). Clin. Anat. 26:975–979, 2013. © 2013 Wiley Periodicals, Inc.